2018
DOI: 10.1536/ihj.17-686
|View full text |Cite
|
Sign up to set email alerts
|

Persistent QT Prolongation in a Child with Gitelman Syndrome and <i>SCN5A</i> H558R Polymorphism

Abstract: Gitelman syndrome (GS) is an inherited renal tubular disorder characterized by hypokalemic metabolic alkalosis, hypomagnesemia, and low urinary calcium excretion. While it is considered a benign disease, severe ventricular arrhythmia and sudden cardiac death related to the prolongation of the QT interval have been reported in rare cases. Herein we report a 13-year-old girl with GS who presented with persistent prolongation of the QT interval, even after being treated for hypokalemia and hypomagnesemia. Genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Early age of onset is associated with severity in many genetic diseases. Although there are many isolated case-reports of SCN5A -channelopathy in children in the medical literature [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], few studies have analyzed SCN5A -channelopathy cohorts where onset of symptoms occurs in pediatric patients. A large prospective multi-center pediatric cohort of SCN5A mutation-positive neonates reported that 67.9% were asymptomatic at diagnosis, while age <1 year at diagnosis, compound heterozygous mutations, and mutations with both gain- and loss-of-function were identified as independent risk factors for cardiac events [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early age of onset is associated with severity in many genetic diseases. Although there are many isolated case-reports of SCN5A -channelopathy in children in the medical literature [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ], few studies have analyzed SCN5A -channelopathy cohorts where onset of symptoms occurs in pediatric patients. A large prospective multi-center pediatric cohort of SCN5A mutation-positive neonates reported that 67.9% were asymptomatic at diagnosis, while age <1 year at diagnosis, compound heterozygous mutations, and mutations with both gain- and loss-of-function were identified as independent risk factors for cardiac events [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to monitor and correct serum electrolyte disturbances to prevent ventricular arrhythmias and sudden death in patients with the condition. In the study by Tsukakoshi et al (2018) the author describes that the H558R polymorphism increases the level of expression of the sodium channel and can therefore affect the initial phase of the action potential, however its effects on the QT interval in the present case were unclear.…”
Section: Discussionmentioning
confidence: 64%
“…Also, impaired renal function may induce higher drugs and catabolite levels, favoring pro-arrhythmias (Reiffel and Appel, 2001). Furthermore, inherited salt-wasting renal disorders, such as Gitelman and Bartter syndromes, provoking hypokalaemia or hypomagnesemia, may favour pro-arrhythmias upon exposure to additional clinical stressors of repolarization, such as QT prolonging cardiac and non-cardiac drugs (Pachulski et al, 2005;Tsukakoshi et al, 2018).…”
Section: Factors Favouring Proarrhythmic Effects Of Drugsmentioning
confidence: 99%